2022
DOI: 10.1038/s41562-021-01278-3
|View full text |Cite
|
Sign up to set email alerts
|

The ephemeral effects of fact-checks on COVID-19 misperceptions in the United States, Great Britain and Canada

Abstract: Widespread misperceptions about COVID-19 and the novel coronavirus threaten to exacerbate the severity of the pandemic. We conducted preregistered survey experiments in the United States, Great Britain and Canada examining the effectiveness of fact-checks that seek to correct these false or unsupported beliefs. Across three countries with differing levels of political conflict over the pandemic response, we demonstrate that fact-checks reduce targeted misperceptions, especially among the groups who are most vu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
27
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(54 citation statements)
references
References 36 publications
1
27
1
Order By: Relevance
“…Furthermore, Emotional Epidemiology even works for rare diseases, such as meningitis. In fact, diseases with high case-fatality rates and epidemic potential recall ghosts of the past and trigger collective defence mechanisms, whose dynamics are consistent with the transmissibility of the same infectious agents [ 19 , 20 ]. In these cases too, the high level of outrage leads to a demand for mass vaccination by the public, as soon as there is even a single episode, only to see the same public quickly lose their perception of the risk soon afterwards.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, Emotional Epidemiology even works for rare diseases, such as meningitis. In fact, diseases with high case-fatality rates and epidemic potential recall ghosts of the past and trigger collective defence mechanisms, whose dynamics are consistent with the transmissibility of the same infectious agents [ 19 , 20 ]. In these cases too, the high level of outrage leads to a demand for mass vaccination by the public, as soon as there is even a single episode, only to see the same public quickly lose their perception of the risk soon afterwards.…”
Section: Introductionmentioning
confidence: 99%
“…This shows that, as with immunological memory with regard to SARS-CoV-2, the memory of scientific data also tends to decline over time due to emotional factors. This illustrates why institutions must also administer booster doses of medical–scientific messages, conveyed correctly and appropriately [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Although some public officials have endorsed the COVID-19 vaccine, others have fostered vaccine hesitancy by broadcasting misinformation (ie, inaccurate health information), which is often disseminated widely via social media [ 7 , 8 ]. The prevalence of US adults who indicate they primarily get news information from social media (ie, 68%) [ 9 ] has given rise to an infodemic , wherein public confidence in the COVID-19 vaccine is shaken by the overload of COVID-19 misinformation on social media [ 10 - 12 ]. Indeed, Loomba et al found that exposure to COVID-19 vaccine misinformation significantly decreases the intention to receive the COVID-19 vaccine [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, to assess how effective vaccination campaigns are against COVID-19 misinformation, such as fact-checking messages on social media, it is important to investigate the actual impact on the public's attitude toward the COVID-19 vaccine. Previous experimental studies have shown that fact-checking interventions can promote people’s positive attitude toward vaccines and increase the accuracy of beliefs about vaccination [ 12 , 23 ]. However, empirical observational evidence for fact-checking messages’ effects on the public's attitude toward the COVID-19 vaccine in the real world is still lacking.…”
Section: Introductionmentioning
confidence: 99%
“…2021 could be called the Year of the Vaccine, when according to the British weekly The Economist [ 8 ] scientists “showed how vaccines and medicines can save hundreds of millions of lives”, or mRNA’s breakout year [ 9 ] with a totally different perspective on drugs, and the word vax —as a shorthand for a vaccine—was declared Word of the Year [ 10 ]. Once again, we chemists have proven ourselves to be innovators in solving problems in the service of mankind.…”
Section: Introductionmentioning
confidence: 99%